2008
DOI: 10.1001/archneurol.2007.23
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging White Matter Hyperintensities and Brain Volume in the Prediction of Mild Cognitive Impairment and Dementia

Abstract: To determine whether magnetic resonance imaging (MRI) white matter hyperintensities (WMH), whole-brain atrophy, and cardiovascular risk factors predict the development of cognitive decline and dementia.Design: Subjects were recruited into this prospective cohort study and followed for incident cognitive decline for mean (SD) 6.0 (4.1) years. Magnetic resonance imaging dual-echo sequences, obtained at baseline, were used to determine the volume of WMH and the brain parenchymal fraction (BPF), the proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
162
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(172 citation statements)
references
References 52 publications
6
162
0
Order By: Relevance
“…24 Furthermore, in a recent longitudinal analysis found that increased white matter hyperintensities could be a predictor of progression from normal to MCI. 31 Association of silent cerebral infarctions with the development of MCI was also reported in another community-based longitudinal study. 32 By considering these findings together with our present data, asymptomatic cerebrovascular damages were thought to be one of possible mechanisms explainable for the relation between abnormal nocturnal BP profile and MCI in apparently healthy elderly persons.…”
Section: Discussionmentioning
confidence: 53%
“…24 Furthermore, in a recent longitudinal analysis found that increased white matter hyperintensities could be a predictor of progression from normal to MCI. 31 Association of silent cerebral infarctions with the development of MCI was also reported in another community-based longitudinal study. 32 By considering these findings together with our present data, asymptomatic cerebrovascular damages were thought to be one of possible mechanisms explainable for the relation between abnormal nocturnal BP profile and MCI in apparently healthy elderly persons.…”
Section: Discussionmentioning
confidence: 53%
“…Although some evidence suggests that WMH may increase the risk of MCI, data come mainly from studies that included small or highly selected samples (i.e., clinic‐based persons), used semi‐quantitative ratings of WMH, and did not involve annual assessments of cognition 2, 8, 9. Furthermore, findings are inconsistent; whereas one study of 67 cognitively intact persons found that WMH were associated with the development of MCI, a considerably larger study did not, particularly when other MRI indices were included in the analyses 8, 9. The degree to which WMH contribute to progressive cognitive decline among older persons initially free of cognitive impairment also is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…8 Cognitive dysfunction has been studied extensively in persons with WMH lesions on MRI. 9,[11][12][13][14][15][16][17][18] Perceived cognitive dysfunction as measured by Cognitive Difficulties Scale was found to be worse with higher WMH burden and the annual rate of decline on the minimental status examination (MMSE) was 0.035 points per standard deviation increase in periventricular WMH. 19 In Importantly, among patients with a history of stroke and/or transient ischemic attack in the Perindopril Protection Against Recurrent Stroke Study (PROGRESS), the dementia risk during a median follow-up period of 3.9 years was found to be 7.7 times higher in patients with white matter disease than those without it at the time of study enrollment.…”
Section: Cognitive Functionmentioning
confidence: 96%